2010
DOI: 10.1097/aln.0b013e3181eff6b7
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Preconditioning Elicits Competent Endogenous Mechanisms of Protection from Oxidative Stress in Cardiomyocytes Derived from Human Embryonic Stem Cells

Abstract: Background Human embryonic stem cell (hESC)-derived cardiomyocytes potentially represent a powerful experimental model complementary to myocardium obtained from patients, relatively inaccessible for research purposes. We tested whether anesthetic-induced preconditioning (APC) with isoflurane elicits competent protective mechanisms in hESC-derived cardiomyocytes against oxidative stress to be used as a model of human cardiomyocytes for studying preconditioning. Methods H1 hESC cell line was differentiated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 47 publications
9
54
0
2
Order By: Relevance
“…Although the mechanisms underlying the protective effect of anaesthetic-induced preconditioning have been shown to resemble those responsible for IPC (Zaugg et al, 2003), Mullenheim et al showed that administration of sevoflurane combined with IPC can synergistically protect rabbit hearts against myocardial infarction indicating the existence of parallel protective mechanisms (Mullenheim et al, 2003). In ESC-derived cardiomyocytes, brief exposure to the commonly used volatile anaesthetic, isoflurane, significantly attenuated cell death against oxidative stress through opening of mitoKATP channels, production of signalling ROS and inhibition of mPTP opening (Sepac et al, 2010). Other benefits include enhanced cell growth capacity and increased expression of pro-angiogenic VEGF as demonstrated in human EPCs preconditioned with sevoflurane (Lucchinetti et al, 2009).…”
Section: Anaestheticsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the mechanisms underlying the protective effect of anaesthetic-induced preconditioning have been shown to resemble those responsible for IPC (Zaugg et al, 2003), Mullenheim et al showed that administration of sevoflurane combined with IPC can synergistically protect rabbit hearts against myocardial infarction indicating the existence of parallel protective mechanisms (Mullenheim et al, 2003). In ESC-derived cardiomyocytes, brief exposure to the commonly used volatile anaesthetic, isoflurane, significantly attenuated cell death against oxidative stress through opening of mitoKATP channels, production of signalling ROS and inhibition of mPTP opening (Sepac et al, 2010). Other benefits include enhanced cell growth capacity and increased expression of pro-angiogenic VEGF as demonstrated in human EPCs preconditioned with sevoflurane (Lucchinetti et al, 2009).…”
Section: Anaestheticsmentioning
confidence: 97%
“…During embryonic development, hepatocytes are differentiated from the definitive endoderm and the definitive endoderm is generated from the mesendoderm, which is induced under the influence of Nodal, a transforming growth factor beta (TGF-beta) family gene product (Zaret, 2000;. The hepatocyte differentiation from the definitive endoderm or mesendoderm is induced by FGF signalling from the cardiac mesoderm and BMP-4 signalling from the septum transversum mesenchyme (Duncan, 2003;Si-Tayeb et al, 2010;Zaret, 2001). Thus, the procedure for induction of hepatocyte differentiation from pluripotent stem cells consists of two steps: the first is definitive endoderm induction by activin, which acts in a similar way to Nodal, the second is hepatocyte induction by FGF and BMP-4.…”
Section: How To Obtain Hepatocytes 21 Hepatocyte Induction By Differmentioning
confidence: 99%
“…In addition, we found that the cardiac muscle phenotype of the P19-derived cardiomyocytes was maintained when growing on collagen, a commonly used natural material in tissue engineering A similar cardiac muscle cell enrichment strategy has been employed using human and mouse ESCs, in which a MHC promoter drove antibiotic resistance or GFP expression [39][40][41][42][43][44][45][46][47]. A previous publication reported an 99% purity for human ESC-derived cardiomyocytes used the α-MHC promoter driving neomycin resistance approach [44].…”
Section: -Discussionmentioning
confidence: 99%
“…Cardiomyocytes are dependent on their cell-cell and extracellular matrix interactions for survival, and thus are also sensitive to disruption, as reviewed in Robey et al, 2008). Strategies improving cardiomyocyte survival have been reported, and include reducing cardiomyocyte loss during transplantation by using a mixture of anti-apoptotic factors and prosurvival factors , treating dissociated cardiomyocyte cultures with a ROCK inhibitor , protecting cardiomyocytes from oxidative stress using isoflurane anesthetic preconditioning (Sepac et al, 2010), co-culturing dissociated cardiomyocytes with embryonic fibroblasts to improve attachment to substrates and EB formation , re-aggregating the cells following dissociation and cell sorting (Hattori et al, 2009;, and heat shock treatment conditioning (Zhang et al, 2001). …”
Section: -Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying the protective effect of anaesthetic-induced preconditioning have been shown to resemble those responsible for IPC (Zaugg et al, 2003), Mullenheim et al showed that administration of sevoflurane combined with IPC can synergistically protect rabbit hearts against myocardial infarction indicating the existence of parallel protective mechanisms (Mullenheim et al, 2003). In ESC-derived cardiomyocytes, brief exposure to the commonly used volatile anaesthetic, isoflurane, significantly attenuated cell death against oxidative stress through opening of mitoK ATP channels, production of signalling ROS and inhibition of mPTP opening (Sepac et al, 2010). Other benefits include enhanced cell growth capacity and increased expression of pro-angiogenic VEGF as demonstrated in human EPCs preconditioned with sevoflurane (Lucchinetti et al, 2009).…”
Section: Anaestheticsmentioning
confidence: 99%